P55 The efficacy and effectiveness of 5-holed salt shakers for reducing salt dispensed by fish and chip shops. (13th September 2016) - Adams, J; Doherty, A; Wrieden, W; Goffe, L; Hillier-Brown, F; Lake, AA; Araujo-Soares, V; Summerbell, C; White, M; Adamson, AJ
Abstract : Background: Standard portions of takeaway fish and chips contain around half the recommended maximum daily intake of salt for adults. One method to reduce this, encouraged by many English local authorities, is using salt shakers with five, instead of the standard 17, holes. The efficacy and effectiveness of these are not known. We sought to determine if: the amount of salt delivered by 5-holed salt shakers (5 HSS) and 17-holed salt shakers (17 HSS) differs under controlled conditions; if any differences are robust to variations in: amount of baseline salt in the shaker, time spent shaking, and the person serving; and if any differences translate into practice. Methods: Four experiments were conducted comparing the amount of salt delivered by shakers. Independent variables were: type of shaker (5 HSS, 17 HSS), amount of baseline salt in the shaker (full, half full, nearly empty), time spent shaking (3 s, 5 s, 10 s), and individual serving. Servers were a convenience sample (n = 10). In each trial, participants performed ten repeats of each condition, alternating between 5 HSS and 17 HSS. Data were analysed using repeated-measures ANOVA in Stata v14.0. One standard portion of fish and chips, with server-added salt, was purchased from all Fish @ Chip Shops in Gateshead and Stockton-on-Tees (n = 60) and shaker used noted. Meals were laboratory analysed to determine salt content. Data were analysed using a t-test. Results: Across all trials, the 17 HSS delivered a mean (SD) of 7.86 g (4.54) per trial, whilst the 5 HSS delivered 2.65 g (1.22) – a 66.3% reduction. There was a significant difference in salt delivered between shakers when other independent variables were kept constant (F(1, 9)=30.79, p < 0.001). This difference was robust to variations in other independent variables (ps < 0.001). Twenty-nine (48.3%) shops used the 5 HSS and 31 the 17 HSS. Mean (SD) salt content of meals from shops using the 17 HSS was 2.94 g (1.30), and 2.63 g (0.83) from shops using the 5 HSS – a 10.8% reduction. There was no difference in salt content of meals from shops using different shakers (t = 1.12, df = 59, p = 0.266). Conclusion: Whilst 5 HSS deliver significant reductions in salt in laboratory conditions, we were unable to detect similar reductions in practice. This may be because server-added salt makes up a small proportion of total salt in meals; and/or differences in how 5 HSS vs 17 HSS are used in practice. Additional measures may be required to substantially reduce the salt content of takeaway food. Fish and Chip Shops in Gateshead and Stockton-on-Tees may not be representative of those across the UK.